A study of alanine aminotransferase - aspartate aminotransferase as a marker of advanced alcoholic liver disease - N., Aravind G.; K., Abhilash; Farooq, Syed Umar (International Journal of Advances in Medicine, 2020)
Background: Alcohol is one of the most common etiology for chronic liver disease. There are several enzymes which remain elevated in both excessive Alcohol consumption and Alcohol induced liver cirrhosis1. But none is sensitive or specific. The ratio of Aspartate transaminase (AST) with Alanine transaminase (ALT) is one of the best marker for alcohol liver disease. Current study mainly compares the ratio of AST/ALT with both Alcoholic liver disease and excessive Alcohol consumption patients. Methods: Observational, cross sectional study conducted on 50 patients diagnosed with alcoholic liver disease and 50 patients of alcohol withdrawal syndrome. Either admitted or seen on outpatient basis at Bangalore medical college and research institute and data was compared among the groups and appropriate statistical methods are applied. Results: The mean ratio of AST/ALT ratio in 50 patients of alcoholic liver disease group was 3.45, whereas the mean ratio in 50 patient of alcohol withdrawal was about 99. When compared statistically this ratio was significant in chronic liver disease group. Conclusions: Most of the patients with heavy alcohol drinking had high AST and alt levels. But ratio of AST/ALT levels was significant high and suggest chronic liver disease secondary to alcohol.